GLOBAL WARMING DAN PENGARUHNYA TERHADAP KARAKTERISTIK GELOMBANG LAUT DI PANTAI TIMUR PULAU BINTAN YANG DITINJAU DARI PERSPEKTIF KLIMATOLOGI - Illona, Dea Jessi; Jaya, Yales Veva; Koenawan, Chandra Joei; Suhana, Mario Putra (Pusat Penelitian Sumberdaya Pesisir dan Laut, Universitas Maritim Raja Ali Haji, Indonesia, 2018)
The influence of global warming has impact on physics oceanographic conditions such as rising sea surface temperature (SST). Beside that, the increase of temperature will affect to climate change which also increase the global wind speed so it will has implied for future ocean wave height. In this study aims to determine the characteristics of ocean wave at the east coast Bintan Island. Hind casting of ocean wave start by processing sea surface wind by downloaded from European Centre for Medium-Range Weather Forecasts (ECMWF), data will be extracted through Ocean Data View (ODV) and analyzed by using wind rose. The characteristic of wind used for calculation effective fetch length for referred to Sverdrup Munk Bretschneider (SMB) method. Fluctuation of SST will be compared to ocean wave height. Result of this study showed that there were differences in the character of ocean waves on a small scale between 1985-1989 as the year that rising temperature have not yet assumed significantly and 2001-2005 temperature begin increase intensively. The pattern of ocean wave at the east coast Bintan Island effected by seasonal wind that moves periodically with the two highest wind speed from north and south, along with lowest speed is during the transition.